(untitled) (Nepal Agriculture Research Journal, 2010)
A total of 36 rice breeding lines including checks were evaluated for resistance to blast at Rampur during 2000-2001. The experiments were conducted under both field condition and greenhouse inoculated condition. Qualitative resistance in rice to blast was assessed based on lesion type, whereas quantitative resistance was assessed based on area under disease progress curve (AUDPC) in the upland field condition. The number of sporulating lesions and the number of leaves with at least one sporulating lesion per plant were considered as measures for evaluation of quantitative resistance in the greenhouse assay. The lesion type, neck blast percentage and AUDPC data suggest that most of the rice lines possess higher level of resistance to leaf and neck blast. The rice lines varied for the number of sporulating lesions and the number of leaves with sporulating lesion per plant. Some lines were incompatible to virulent blast isolates, showing major resistance genes. NR 1558, NR 601-1-1-9, BW306-2 and CN 836-3-10 were promising lines for quantitative resistance to both leaf and neck blast. Radha 12, Sabitri, Janaki possess higher level of quantitative resistance to blast, hence these could be promoted for cultivation in blast-prone environments. These genotypes could also be utilized as donor parents for breeding durable blast resistant varieties. The most virulent blast isolate could be used for evaluation of both qualitative and quantitative resistance to blast in early generation in the greenhouse so that workload could be cut down in future works. Key words: Blast resistance; field condition; greenhouse assay; Pyricularia grisea; rice lines DOI: 10.3126/narj.v6i0.3344 Nepal Agriculture Research Journal Vol.6 2005 pp.49-56